Lignosus rhinocerotis Cooke Ryvarden ameliorates airway inflammation, mucus hypersecretion and airway hyperresponsiveness in a murine model of asthma - Johnathan, Malagobadan; Muhamad, Siti Aminah; Siew, Hua Gan; Stanslas, Johnson; Mohd Fuad, Wan Ezumi; Hussain, Faezahtul Arbaeyah; Wan Ahmad, Wan Amir Nizam; Abdullah, Nurul Asma (Public Library of Science, 2021)
Lignosus rhinocerotis Cooke. (L. rhinocerotis) is a medicinal mushroom traditionally used in the treatment of asthma and several other diseases by the indigenous communities in Malaysia. In this study, the effects of L. rhinocerotis on allergic airway inflammation and hyperresponsiveness were investigated. L. rhinocerotis extract (LRE) was prepared by hot water extraction using soxhlet. Airway hyperresponsiveness (AHR) study was performed in house dust mite (HDM)-induced asthma in Balb/c mice while airway inflammation study was performed in ovalbumin (OVA)-induced asthma in Sprague-Dawley rats. Treatment with different doses of LRE (125, 250 and 500 mg/kg) significantly inhibited AHR in HDM-induced mice. Treatment with LRE also significantly decreased the elevated IgE in serum, Th2 cytokines in bronchoalveolar lavage fluid and ameliorated OVA-induced histological changes in rats by attenuating leukocyte infiltration, mucus hypersecretion and goblet cell hyperplasia in the lungs. LRE also significantly reduced the number of eosinophils and neutrophils in BALF. Interestingly, a significant reduction of the FOXP3+ regulatory T lymphocytes was observed following OVA induction, but the cells were significantly elevated with LRE treatment. Subsequent analyses on gene expression revealed regulation of several important genes i.e. IL17A, ADAM33, CCL5, IL4, CCR3, CCR8, PMCH, CCL22, IFNG, CCL17, CCR4, PRG2, FCER1A, CLCA1, CHIA and Cma1 which were up-regulated following OVA induction but down-regulated following treatment with LRE. In conclusion, LRE alleviates allergy airway inflammation and hyperresponsiveness, thus suggesting its therapeutic potential as a new armamentarium against allergic asthma.